Hipoalbuminemia como factor de riesgo de dehiscencia de anastomosis intestinal - Castillo García, Carmen Guadalupe (2022)
Bowel anastomotic complications are associated with increased patient mortality and morbidity, including the potential need for urgent reoperation and prolonged hospitalization. One of the most feared complications is intestinal anastomosis dehiscence, which will be defined as that clinical manifestation that includes: 1) the exit of intestinal content or gases through a drain, from the main wound or fistulization to an organ neighbor and/or, 2) the findings of a reintervention for localized (collection) or generalized peritonitis secondary to an anastomotic leak, 3) computed tomography that showed contrast leakage, collection or peranastomotic bubble. Its prevalence varies between 2% and 5% in the different series, and it is variable in patients with trauma, cancer or benign disease, as well as in colorectal surgeries, where its incidence varies widely in the publications between 1.8-19%. Being higher in rectal surgery, the existence of multiple interrelated risk factors that favor this condition must also be considered. There are multiple studies that correlate malnutrition and hypoalbuminemia with an increase in the rate of anastomosis dehiscence. Hypoalbuminemia is a clinical condition in which there is a decrease in serum albumin levels below 3.5 g/dl; it can be of multifactorial etiology and a common finding in some hospitalized patients, especially if they are in a critical or terminal condition; hence the need to study the association between these conditions in our population.